The effectiveness and determinants of effectiveness of antiretroviral therapy for adults in the Western Cape Province of South Africa - Boulle, Andrew (Department of Public Health and Family Medicine, 2023)
Antiretroviral therapy (ART) first became available in the public sector in the Western Cape Province in Khayelitsha in 2001. This thesis describes the effectiveness of ART in Khayelitsha and the Province, following adult patients for up to five years on ART, and examining temporal trends over seven years during which time the availability of ART in the Province increased dramatically. Associations are explored with a range of clinical outcomes, and regimen durability and tolerability are described, together with regimen effectiveness when ART is administered to patients co-infected with tuberculosis. The results chapters of the thesis are presented in the form of published or submitted papers. The first paper corrects for under-ascertainment of mortality through linkages with the death registry. After five years on ART, four out of five patients were still alive. Survival did not deteriorate in more recent years despite the large increase in patient numbers. Patients who remained virologically suppressed experienced on average continued CD4 count recovery throughout follow-up to five years. The second paper describes the tolerability of each commonly used first-line antiretroviral drug in two townships in the Western Cape. Treatment-limiting toxicities were frequent and continued throughout follow-up in patients on stavudine (21% by 3 years on ART). Symptomatic hyperlactataemia or lactic acidosis as well as lipodystrophy were strongly associated with women initiating ART with a high initial body mass. The third paper explores the effectiveness of ART when co-administered with tuberculosis treatment, identifying that co-infected patients initiating nevirapinebased ART may be at a higher risk of virological failure, but that concurrent tuberculosis treatment did not otherwise compromise ART outcomes. The fourth paper, based on a household survey, provides an in-depth description of the Khayelitsha population demonstrating comparability with many of the urban settings in which ART is provided in the region. The final paper demonstrates that outcomes have not been compromised by the wider availability of ART in the Western Cape Province. The thesis concludes that the Khayelitsha and Provincial analyses provide considerable reassurance that the anticipated benefits of ART have not to date been eroded by health system weaknesses or contextual challenges.